Differences of circulating Bordetella pertussis population in Argentina from the strain used in vaccine production - Fingermann, Matías (2006)
In Argentina, as in other countries, the number of pertussis cases has been increasing, even in highly vaccinated zones. Many reports suggest that the decline of vaccine efficacy due to antigenic shifts in the circulating Bordetella pertussis might be among the factors that contribute to pertussis re-emergence in different parts of the world. To evaluate the incidence of this factor in Argentina, we decided to characterize the circulating bacteria of an important demographic area of this country in comparison with the strain used for vaccine production. From 1997 to 2003 we collected nasopharyngeal samples from pediatric patients with signs of Bordetella infection hospitalized in the metropolitan area of Buenos Aires and La Plata, Argentina. From these samples we identified 28 B. pertussis, which were characterized by biochemical techniques, PCR, DNA fingerprint, prn and ptx genes sequencing, and lipopolysaccharides (LPS) pattern. BOX-PCR from B. pertussis isolates yielded one cluster containing 13 isolates and some smaller ones, being all fingerprints different from the vaccine strain. Differences between Argentinean circulating bacteria and the vaccine strain were also observed for the Prn and Ptx variants as well as for the LPS pattern. Moreover, this last pattern seemed to change over the years. In addition, we identified two B. bronchiseptica. The presence of this Bordetella species together with the observed differences between circulating B. pertussis and the strain used in vaccine production should be considered for the development of an improved vaccine.